Adaptive approach to processing data of experts evaluation when solving problems in the field of information protection - Архипов, Александр Евгеньевич; Архипова, София Анатольевна (Ukrainian Information Security Research Journal, 2019)
Expert procedures are effective, and in some cases the only way to obtain the information necessary to solve a wide range of tasks in the field of information protection. The article analyzes the accuracy aspects of the processing of group examination data, in particular, the possibility of realizing the optimal processing of this data. It is shown that an attempt to formulate and solve the optimization problem in the most complete statement leads to a conflict situation due to the lack of the necessary a priori information for the correct solution of the problem in this statement. The way out is the use of an adaptive approach to organizing data processing, the essence of which is to extract the missing information directly from the processed data set. The additional information received, to one degree or another, makes up for the deficit of a priori information, ensuring the improvement of the structure and functions of the elements of the processing procedure. Improving the processing procedure increases its efficiency and allows you to further expand the amount of additional information received, causing the implementation of a new adaptation step. As a result, an iterative process mode of adaptive data processing is formed, the concept of the adaptation level is introduced, its methodological and operational content, model representations of the basic elements of the adaptation procedure are considered. Possible levels of adaptation, their substantive aspect, methods of accumulating and storing information about the properties of expert data and characteristics of experts are described, the criteria and methodology for making decisions about data processing methods and forms of their implementation are considered.